A Fully Digital Workflow for Transferring an Emergence Profile in the Esthetic Zone: A Case Report - Aslıhan Öztürk; Barış Güncü (Clinical Dentistry and Research, 2026)
Preservation of peri-implant soft tissue contours is criticalfor achieving esthetic outcomes in implant-supportedrestorations in the anterior region. Transferring the emergenceprofile shaped with a provisional restoration to the definitiveprosthesis remains challenging in digital workflow. In this case,peri-implant soft tissue shaping for an implant-supportedrestoration in the maxillary left central incisor region, and aftersoft tissue maturation, digital records were obtained usingan intraoral scanner and transmitted to the dental laboratory.First, with the screw-retained provisional restoration in place,the maxillary and mandibular arches, as well as the interocclusalrelationship, were scanned. Second, after removal of the screwretainedprovisional restoration, the peri-implant soft tissuewas scanned to record the emergence profile, followed byscanning with an implant scan body. Third, the provisionalrestoration was scanned while screwed onto an implantanalog. For shade selection, photographs were taken using asmartphone with a gray card and a shade guide. The acquiredimages were calibrated for white balance using a photo editingsoftware and then forwarded to the dental laboratory. Alldigital datasets were aligned within dental design software,and a monolithic zirconia restoration with a buccal cutback wasdesigned. The zirconia restoration was fabricated accordingto the principles of the ‘Esthetic Biological Contour Concept’.The surfaces contacting the peri-implant soft tissues werepolished, and the final restoration was delivered to the patient.This workflow simplified the clinical procedures, minimized softtissue distortion, and facilitated a predictable transfer of theemergence profile.